Model Regresi Faktor-Faktor Yang Mempengaruhi Ekspor Kopi Indonesia Ke Jepang - Sukmaya, Syahrul Ganda; Harmaidi, Desma (Jurnal E-Bis, 2025)
The phenomenon of fluctuations in Indonesian coffee exports to Japan shows complex dynamics influenced by various external and internal factors. This study aims to analyze the effect of world coffee prices, climate conditions, and trade promotion on the volume of Indonesian coffee exports to Japan. The method used is multiple regression analysis with a time series approach using data from 1989 to 2024. The results show that simultaneously, all independent variables—world coffee prices, air temperature, rainfall, exchange rate volatility, and trade promotion dummy—have a significant effect on export volume. Partially, world coffee prices have a significant positive effect, while air temperature and trade promotion dummy have a significant negative effect. Rainfall and exchange rate volatility have no significant effect.